Corporate Communications and Corporate Social Responsibility of Coal Mining Companies in Promoting Community Well-being - Dian Ratu Ayu Uswatun Khasanah; Hafri Yuliani; Titi Darmi; Ronald Jolly Pongantung (DAWUH : Islamic Communication Journal, 2026)
Corporate Social Responsibility (CSR) represents both a moral and legal obligation of corporations to promote the welfare of communities within their operational sphere. In the coal mining sector in Indonesia, effective CSR implementation is inseparable from the quality of corporate communication the strategic process through which companies convey their social commitments, build trust with stakeholders, and manage their public image before affected communities. This research examines: (1) the normative framework of CSR for coal mining companies under applicable Indonesian legislation, encompassing the most recent regulations including Law No. 3/2020, Law No. 11/2020, Government Regulation No. 96/2021, and Government Regulation No. 25/2024; and (2) the reconstruction of an ideal CSR communication model within a welfare state perspective to improve community well-being. Employing a normative juridical approach with qualitative descriptive-analytical data analysis, this study reveals that despite the relatively comprehensive legal foundation for CSR in Indonesia, significant weaknesses persist in the form of inter-regulatory disharmony, insufficient deterrent sanctions, and unsystematic oversight mechanisms. Furthermore, deficiencies in corporate communication practices — including asymmetric information dissemination, lack of transparent dialogue, and absent participatory communication — exacerbate the gap between normative CSR obligations and their real-world impact. Accordingly, a comprehensive reconstruction of the mining CSR system is needed, encompassing regulatory harmonization, institutional strengthening, corporate paradigm transformation, and meaningful community participation facilitated through effective multi-stakeholder communication. Keywords: Corporate Communication; Corporate Social Responsibility; Coal Mining; Community Welfare; Normative Juridical.